Cadmium sulfide interface layer for improving the performance of titanium dioxide/poly (3-hexylthiophene) solar cells by extending the spectral response - Thanihaichelvan, M.; Sockiah, K.; Balashangar, K.; Ravirajan, P. (University of Jaffna, 2015)
This work focused on studying the effect of cadmium sulfide (CdS) interfacial layer on the performance of titanium dioxide (TiO2)/poly (3-hexylthiophene) (P3HT) solar cells and finding out its effect on charge recombination dynamics of hybrid TiO2/P3HT solar cells. FESEM images confirm the uniform distribution of chemical bath deposited CdS layer on TiO2 nanoparticles. Insertion of CdS layer at the nanocrystalline TiO2/P3HT interface broadens quantum efficiency spectrum of the solar cells with peak values over 80 and 40 % at the wavelengths of maximum absorption of CdS and P3HT respectively and hence enhances short-circuit current density (JSC) from 3.5 to 5.9 mAcm-2 under simulated illumination (70 mWcm-2 ) with an AM 1.5 filter. CdS layer further improves open circuit voltage (VOC) from 0.35 to 0.57 V, which is consistent with higher built-in voltage in CdS/P3HT than in TiO2/P3HT due to relatively lower laying conduction band edge of CdS. Photovoltaic transient measurements show that the carrier life-time in TiO2/CdS/P3HT solar cell is an order of magnitude longer than that in TiO2/P3HT solar cell. Optimized TiO2/P3HT solar cells with CdS interlayer yield power conversion effi ciencies over 1.5 %, which is three times greater than that for similar solar cells without CdS layer.